Ultrastructural and functional characteristics of human spermatozoa after cryopreservation by vitrification - Pavlovych , Olena; Hapon , Hanna; Yurchuk , Taisiia; Repin , Mykola; Marchenko , Larysa; Govorukha , Tetiana; Petrushko , Maryna (Problems of Cryobiology and Cryomedicine, 2020)
Low temperature preservation of spermatozoa is widely applied in infertility treatment when using the assisted reproductive technology (ART). There are the standard methods for ejaculated spermatozoa cryopreservation in normozoospermia, but their application for ejaculate-derived spermatozoa, having spermatogenesis defects, is impossible. Therefore, of high priority are to design the cryopreservation methods and assess morphofunctional and ultrastructural characteristics of spermatozoa after cryopreservation. Here, we have evaluated the impact of cryopreservation by vitrification using non-penetrating cryoprotectants of polyvinylpyrrolidone (PVP) and sucrose on morphofunctional and ultrastructural state of human spermatozoa in pathospermia. In (22.3 ± 3.4),(26.8 ± 4.2), (18.6 ± 2.1)% of spermatozoa after vitrification with 0.25M sucrose; 10% PVP and a mixture of 0.25 M sucrose, 10% PVP, 10% HSA, respectively, we have observed the appearance of vacuoles in nuclear chromatin of spermatozoa. For freshly isolated spermatozoa this index was (16.6 ± 1.4)%. In the studied groups, the ultrastructural characteristics of acrosome, axoneme, periaxonemal structures, and spermatozoa flagella did not significantly differ from the control samples. The cryopreservation of human spermatozoa by vitrification using sucrose and PVP solutions was shown to preserve their viability and ultrastructural integrity and to be promising in ART. Probl Cryobiol Cryomed 2020; 30(1): 24-33